Amyloid‐related imaging abnormalities from trials of solanezumab for Alzheimer's disease. Issue 1 (1st March 2016) - Carlson, Christopher; Siemers, Eric; Hake, Ann; Case, Michael; Hayduk, Roza; Suhy, Joyce; Oh, Joonmi; Barakos, Jerome
Abstract: Introduction: Solanezumab, a humanized monoclonal antibody that binds soluble amyloid beta peptide, is being developed for treatment of Alzheimer's disease (AD). Methods: Patients (n = 2042) with mild and moderate AD were randomized 1:1 to 400‐mg solanezumab or placebo infusion every 4 weeks for 80 weeks and 1457 patients entered an open‐label extension. Magnetic resonance imaging scans monitored for amyloid‐related imaging abnormalities‐edema/effusion (ARIA‐E) and amyloid‐related imaging abnormalities‐hemorrhage/hemosiderin deposition. Results: Sixteen patients (solanezumab, n = 11; placebo, n = 5) developed ARIA‐E during the double‐blind phase, and 7 patients developed ARIA‐E during the open‐label extension as of July 31, 2014. Unique cases are discussed including solanezumab patients who were given solanezumab, while ARIA‐E was present and a patient who developed ARIA‐E during placebo treatment and again during solanezumab treatment. Discussion: Asymptomatic ARIA‐E was detected in solanezumab‐treated and placebo‐treated AD patients. ARIA‐E occurs infrequently during solanezumab and placebo treatments but may occur repeatedly in some patients.